An ontoepistemological reflection from the position of complexity (Salud, Arte y Cuidado, 2023)
This essay aims to reflect on the ontoepistemological position of the author, to guide the approach to the phenomenon of study in doctoral research; From a hermeneutic-interpretative approach, with a bibliographic documentary method, it begins by considering the position in the philosophical field, through a reflection on the theoretical aspects that will support the technical and practical aspects of the research. The theory of complexity is vindicated and it is concluded that under this vision the use of a dialectical thought or logic is required, in which the parts are inseparable, they constitute an interdependent, interactive fabric; understood from the point of view of the whole in its context and evaluated by the role or function it plays in that whole.
Keywords: philosophical field; onto-epistemological vision; complexity; paradigm